Knowledge and attitude towards dental trauma management among primary school teachers - Baharin, Fadzlinda; Osman, Nor Fatimah; Adnan, Munirah Mohd (Padjadjaran Journal of Dentistry, 2019)
Introduction: Dental injuries could happen anywhere, including in the school compound. Correct management by the teachers in dental emergencies could prevent further damage to the traumatized tooth and improve the success rate of the treatment. Hence, the purpose of this study was to assess the knowledge and attitude towards dental trauma management among the primary school teachers in Kubang Kerian area. Methods: This descriptive study was conducted in three national primary schools in Kubang Kerian and multi-stages sampling was performed to select the subjects. One hundred and twenty teachers (n = 120) were randomly selected and responded to a set of a self-administered questionnaire. The questionnaire consisted of general characteristics, knowledge, and attitude towards dental trauma. Results: A total of 120 primary school teachers, predominantly female teachers (74.2%) participated in this study. More than half of the teachers (62.5%) have more than 15 years of teaching experience. One-third of the teachers (34.2%) have completed first aid training; however, dental trauma management subject was lacking (1.7%). About 31.7% of the respondent had experienced dental trauma case. Eighty-five percent of the teachers did not opt for tooth replantation in the case of avulsion and almost all the teachers (97.5%) did not choose fresh milk as the medium storage of the avulsed tooth. Conclusion: The level of knowledge and attitude on dental trauma management among school teachers is unsatisfactory. As a recommendation, first aid training given to the teachers should include basic knowledge of dental trauma management. The awareness can be improved by organizing talk or campaign on dental trauma management at the school level.Keywords: Children, dental trauma, school teachers.